The diagnostic efficacy of some ischemic markers (urotensin II and urotensin II related peptide) in early diagnosis of intestinal ischemia in experimentally increased intraabdominal pressure in rats - Bozan, Mehmet Bugra; Ayten, Refik; Bülbüller, Nurullah; Camcı, Cemalettin; Aygen, Erhan; İlhan, Necip; Kutluer, Nizamettin (My University, 2019)
Aim: The purpose of this experimental study is evaluating the relation between plasma urotensin-II (U-II) and urotensin-II relatedpeptide (URP) levels with intestinal ischemia caused by elevated intraabdominal pressure.Material-Methods: Wistar albino rats weighing 200–250 grams used.Group-1: Laparatomized group without abdominal pressure elevation in sixty minutes under general anesthesia.Group-2: Ten mmHg elevated intraabdominal pressure group in sixty minutes under general anesthesia.Group-3: Fifteen mmHg elevated intraabdominal pressure group in sixty minutes under general anesthesia.Group-4: Twenty mmHg elevated intraabdominal pressure group in sixty minutes under general anesthesia.After sacrifing, in general anesthesia blood and tissue samples were collected. Hematoxilen and eosyn stained tissue samples wereexamined under light microscope.Results: Plasma U-II levels changes insignificant in group 2 and 3 but in group-4 was changed significantly compared with thecontrol group(respectevely p=0,609; p=0.848; p=0.04). Plasma URP levels changed significantly in all groups compared with thecontrol group (p-values were p=0.018; p=0.018 and p=0.04 respectively).Conclusion: U-II levels could not be a useful parameter for the early diagnosis of the intestinal ischemic damage caused byintraabdominal pressure(IAP), because it is found in all vascular structures. On the other hand, plasma URP levels would be used forthe early diagnosis of the intestinal ischemia. Because of the limitations of our study, we believe that our results should be confirmedwith clinical studies.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Patoloji